Environmental Exposures and Puberty in Inner-City Girls - Wolff, Mary S. (2008)
BACKGROUND: Hormonally active environmental exposures are suspected to alter onset of puberty in girls, but research on this question has been very limited. OBJECTIVE: We investigated pubertal status in relation to hormonally active environmental exposures among a multiethnic group of 192 healthy nine-year old girls residing in New York City. METHODS: Information was collected on breast and pubic hair stages, weight and height. Phytoestrogen intake was estimated from a food frequency questionnaire. Three phytoestrogens and bis-phenolA (BPA) were measured in urine. In a subset, 1,1′-dichloro-2,2′-bis(4-chlorophenyl)ethylene (DDE), polychlorinated biphenyls (PCBs) were measured in blood plasma and lead (Pb) in blood. Associations of exposures with pubertal stages (present=stage 2+ vs absent=stage 1) were examined using t-tests and Poisson multivariate regression to derive prevalence ratios (PR, 95%-confidence limits [CI]). RESULTS: Breast development was present in 53% of girls. DDE, Pb, and dietary intakes of phytoestrogens were not significantly associated with breast stage. Urinary phytoestrogen biomarker concentrations were lower among girls with breast development than with no development. In multivariate models, main effects were strongest for two urinary isoflavones, daidzein (PR 0.89 [0.83-0.96] per ln-μg/g creatinine) and genistein (0.94 [0.88-1.01]). Body mass index (BMI) is a hormonally relevant, strong risk factor for breast development. Therefore, BMI-modification of exposure effects was examined, and associations became stronger. Delayed breast development was observed among girls with below-median BMI and 3rd tertile (high exposure) of urinary daidzein (PR 0.46 [0.26-0.78]); a similar effect was seen with genistein, comparing to girls ≥median BMI and lowest two tertiles (combined) of these isoflavones. With urinary enterolactone a phytoestrogen effect was seen only among girls with high BMI, where breast development was delayed among those with high urinary enterolactone (PR 0.55 [0.32 - 0.96] for the upper tertile vs lower two combined). There was no main effect of PCBs on breast stage, but girls with below-median BMI and ≥median PCB levels had reduced risk for breast development (any vs none) compared with other BMI-PCB groups. No biomarkers were associated with hair development, which was present in 31% of girls. CONCLUSIONS: Phytoestrogens and PCBs are environmental exposures that may delay breast development, especially in conjunction with BMI which governs the endogenous hormonal milieu. Further research to confirm these findings may improve our understanding of the role of early-life development in breast cancer risk and other chronic diseases related to obesity.